Acute alcohol intoxication and bispectral index monitoring. Issue 8 (4th June 2015) - Gerstman, M. D.; Merry, A. F.; McIlroy, D. R.; Hannam, J. A.; Mitchell, S. J.; Myles, P. S.
<x xml:space="preserve">Abstract</x> Background Bispectral index (BIS) monitoring is commonly used to decrease the risk of awareness during anaesthesia. We aimed to determine the relationship between blood alcohol concentration and brain function (as measured by BIS) in healthy adults. Methods In this prospective observational study, 21 anaesthetic registrars self‐regulated alcohol consumption over a 3‐h period. Expired alcohol concentration (breathalyser) and BIS measurements were performed hourly for 4 h. A venous blood alcohol sample was taken at the conclusion of the study period. Results The main outcome measures were the correlation between blood alcohol and brain function as measured by BIS and the change in BIS from baseline (∆BIS) at 4 h. The median number of standard drinks consumed was 9.1 (IQR 7.7–12.3), range 5.4–17. At 4 h, there was a moderate inverse correlation between BIS and blood alcohol (r = −0.49, P = 0.029) and between ∆BIS and blood alcohol (r = −0.46, P =0.043). Conclusion In healthy young adults, we found a moderate correlation between venous blood alcohol concentration and BIS. This suggests that acute alcohol consumption can decrease BIS. This information may be relevant when providing anaesthesia to intoxicated patients who require urgent or time‐critical surgery, although certain limitations of this study should be kept in mind.